Abundance, Morphometrics, Length-Weight Relationship, and Condition Factors of Lola Snails (Rochia Niloticus L) in the Waters of Sarang Island, Belakang Padang, Batam - Dinata, Rifal; Ramses, Ramses; Amelia, Fitrah; Ismarti, Ismarti (Syiah Kuala University, 2025)
Lola snails (Rochia niloticus) are biota that are widely consumed by coastal communities in Batam waters. Even though it is not a favored commodity, exploitation that does not consider sustainability can lead to population scarcity in nature. This research aims to collect comprehensive data regarding the abundance, morphometrics, and weight-length relationship of Lola snails in the waters of Sarang Island, Batam. Sampling was carried out at 3 locations, including Kajang, Piring, and Layang Islands. The Lola snail sampling method was carried out using purposive sampling. Water quality measurements are carried out in situ. Morphometric data were collected by measuring the body dimensions of Lola snails using digital calipers. Abundance was determined based on the number of individuals per unit area, and the length-weight relationship was analyzed using linear regression to determine growth patterns. The research results show that the condition of the aquatic environment still meets the environmental quality standards set by the Ministry of Environment No. 51 of 2004. The abundance of Lola snails was in range of 0.22- 0.97 ind/m2, and the highest was found on Kajang Island. The results of morphometric measurements showed that the highest shell length, weight, and shell width were observed in Lola snail samples from Kajang Island with values of 48.40 25.28 mm, 68.77 101.55 mg, and 44.42 23.28 mm. There is a relationship between the growth patterns of Lola snails caught at three stations which have negative allometric growth patterns, where Kajang Island, Piring Island, and Layang Island have negative allometric growth patterns (b3) with exponential values of 0.9685, 1.5121, and 2.5471, respectively. The value of relative weight condition factor (Wr) shows a value close to 100 on Kajang, Piring, and Layang Island, namely 102.753 and 104.812, 99.654, which indicates that Lola snails were in good condition during the research.